Morbidity Rate of the Retrosigmoid versus Translabyrinthine Approach for Vestibular Schwannoma Resection - Obaid, Sami; Nikolaidis, Ioannis; Alzahrani, Musaed; Moumdjian, Robert; Saliba, Issam (Journal of audiology & otology, 2018)
Controversy related to the choice of surgical approach for vestibular schwannoma (VS) resection remains. Whether the retrosigmoid (RS) or translabyrinthine (TL) approach should be performed is a matter of debate. In the context of a lack of clear evidence favoring one approach, we conducted a retrospective study to compare the morbidity rate of both surgical approaches. Subjects and. 168 patients underwent surgical treatment (2007-2013) for VS at our tertiary care center. There were no exclusion criteria. Patients were separated into two groups according to the surgical approach: TL group and RS group. Signs and symptoms including ataxia, headache, tinnitus, vertigo and cranial nerve injuries were recorded pre- and postoperatively. Surgical complications were analyzed. Perioperative facial nerve function was measured according to House-Brackmann grading system. Tumor resection was similar in both groups. Facial paresis was significantly greater in RS group patients preoperatively, in the immediate postoperative period and at one year follow-up (p<0.05). A constant difference was found between both groups at all three periods (p=0.016). The evolution of proportion was not found to be different between both groups (p=0.942), revealing a similar rate of surgically related facial paresis. Higher rate of ataxic gait (p=0.019), tinnitus (p=0.039) and cranial nerve injuries (p=0.016) was found in RS group patients. The incidence of headache, vertigo, vascular complications, cerebrospinal fluid leak and meningitis was similar in both groups. No reported mortality in this series. Both approaches seem similar in terms of resection efficacy. However, according to our analysis, the TL approach is less morbid. Thus, for VS in which hearing preservation is not considered, TL approach is preferable.